Effect of Different Commercial Feeds on Small Intestine Morphometry and Histomorphometry of Alope Chickens - Muhammad Farhan Hidayatullah; Wempie Pakiding (Jurnal Peternakan Integratif, 2025)
Each commercial feed has different nutritional compositions that may affect the productivity and digestive tract condition of Alope chickens. This study aimed to evaluate the effect of different commercial feeds on the morphometry and histomorphometry of the small intestine in Alope chickens. The experiment was conducted using a Completely Randomized Design with four treatments and three replications: P1 (Commercial Feed X1), P2 (Commercial Feed X2), P3 (Commercial Feed X3), and P4 (Commercial Feed X4). Parameters were small intestine morphometry, weight of the duodenum, jejunum, and ileum and small intestine histomorphometry.  The results showed that different commercial feeds had no significant effect (P>0.05) on intestinal morphometry, except for the weight and length/weight ratio of the jejunum. Conversely, there was a significant effect (P<0.05) on the histomorphometry of the jejunum and ileum. The P3 treatment produced the best results and is recommended as the most effective feed to support small intestine development in Alope chickens.